PENGARUH PERTUMBUHAN PENJUALAN, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR CONSUMER NON CYCLICAL DI BURSA EFEK INDONESIA - Syadilah, Nurul; Dewi, Aminar Sutra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Company Value is a value that reflects the level of success that is being achieved by the company and also provides a summary of the achievement of the financial performance of the business at a certain time to influence the views of potential investors and old investors towards the business. This study aims to examine the effect of Sales Growth, Asset Structure and Company Size on Company Value in the Non-Cyclical Consumer Sector Listed on the Indonesia Stock Exchange in 2019-2023. This type of research is quantitative. The population in this study was 128 companies. The sample in this study was 20 companies taken using the purposive sampling method. The data source in this study is secondary data. The method used in this study is panel data analysis using Eviews version 12. The hypothesis was tested using the t-test at α = 0.05. The results of this study indicate that sales growth and asset structure have a positive and significant effect on company value, while company size does not affect company value.Keywords: Sales Growth, Asset Structure,Firm Size,Firm Value, Non-Cyclical Comsumers